Prevalence and Sociodemographic and Lifestyle Determinants of Anemia during Pregnancy: A Cross-Sectional Study of Pregnant Women in China - Xu, Xianglong (Int J Environ Res Public Health, 2016)
Objective: This study aimed to assess the differences regarding anemia among pregnant women with diverse characteristics and lifestyle factors. Methods: A cross-sectional study of pregnant women was conducted between June and August 2015 in 16 hospitals in five provinces of Mainland China. Self-reported doctor-diagnosed anemia was used in the study. Results: We included 2345 pregnant women. Of the participants, 1755 (74.8%) were pregnant women of first pregnancy (PWFP) and 590 (25.2%) were second pregnancy (PWSP). The mean age of the participants was 28.1 years (SD 4.1). Overall, the prevalence of anemia was 12.7% (13.4% and 10.7% among PWFP and PWSP, respectively). The prevalence for not eating breakfast was 11.0%. Compared with PWFP, PWSP was inversely associated with the risk of anemia (odds ratio (OR) 0.66, 95% CI 0.48–0.91). Compared with those being registered in a low ranking hospital, pregnant women who were admitted to a high (OR 0.40, 95% CI 0.28–0.57) or a medium ranking hospital (OR 0.58, 95% CI 0.37–0.92) were inversely associated with the risk of anemia. Compared with women of low income (<¥4,500), those with high income were less likely to have anemia (OR 0.68, 95% CI 0.50–0.94). Compared with women with non-manual jobs, women with manual jobs (OR 1.70, 95% CI 1.17–2.45) and unemployed women (OR 1.42, 95% CI 1.04–1.93) were associated with a greater likelihood of suffering from anemia. Conclusions: Pregnant women not eating breakfast are of concern. Anemia is highly prevalent among pregnant women in China. Lower socio-economic status, manual jobs, PWFP, and those who attend a lower quality hospital have a greater likelihood of suffering from anemia. Tailored interventions are needed to address these issues.